Effects of Anesthesia Changes During Maintenance ECT: A Longitudinal Comparison of Seizure Quality Under Anesthesia Using Propofol/Esketamine Versus Methohexital - Methfessel, Isabel; Zilles-Wegner, David; Kunze-Szikszay, Nils; Belz, Michael (Pharmacopsychiatry, 2023)
Introduction The effectiveness of ECT relies on the induction of a generalized cerebral seizure. Among others, seizure quality (SQ) is potentially influenced by the anesthetic drug used. Commonly used anesthetics comprise barbiturates, etomidate, propofol, and esketamine, with different characteristics and impacts on seizure parameters. So far, no studies have compared the influence of methohexital vs. a combination of propofol/esketamine on established SQ parameters.Methods This retrospective longitudinal study compared eight established SQ parameters (PSI, ASEI, MSC, midictal amplitude, motor and electroencephalography (EEG) seizure duration, concordance, PHR) before and after the change from propofol/esketamine to methohexital in 34 patients under maintenance ECT. Each patient contributed four measurements, two before and two after the anesthesia change. Anesthesia dose, stimulus dose, electrode placement, and concomitant medication remained unchanged throughout the analyzed treatments.Results Under methohexital (M=88.97 mg), ASEI (p=0.039 to 0.013) and midictal amplitude (p=0.022 to<0.001) were significantly lower, whereas seizure duration (motor and EEG) was significantly longer when compared to propofol/esketamine (M=64.26 mg/51.18 mg; p=0.012 to<0.001). PSI, MSC, seizure concordance, and PHR were not affected by the anesthetic used.Discussion Although to what extent these parameters correlate with the therapeutic effectiveness remains ambiguous, a decision for or against a particular anesthetic could be considered if a specific SQ parameter needs optimization. However, no general superiority for one specific substance or combination was found in this study. In the next step, anesthetic effects on treatment response and tolerability should be focused on.
Keywords: ECT anesthesia; anesthetic change; seizure quality parameters; seizure duration; ASEI